An Analysis of TikTok Addiction in Elementary School Students and Perceptions of Decreased Academic Achievement - Hasanah , Ayu Cahyati; Aksari, Ika Hardiyan; Rahmadanti , Lusiani; Rondli , Wawan Shokib; Santoso, Santoso (Jaanur Elbarik Indonesia, 2025)
This study aims to analyze the level of TikTok addiction in elementary school students and its relationship with parental perceptions of their children's declining academic achievement. This study used a descriptive quantitative approach with a non-experimental correlational research type. The results of the analysis indicate that students' levels of TikTok addiction tend to be quite significant. Meanwhile, parental perceptions of their children's declining academic achievement varied, with most agreeing that TikTok affects their children's learning. Although no statistically significant relationship was found between the two variables, supporting data from teachers indicated that the majority of students experienced disruptions in learning time and decreased academic motivation due to TikTok use.